Faktor 5C dalam Pembiayaan Kepemilikan Rumah di Bank BJB Syariah Kantor Cabang Pembantu Rancaekek - Ida Rapida Djachrab (Masoem University, 2021)
This study aims to provide an overview of the procedure for submitting financing and the application of the 5C principle (character, capacity, capital, collateral, condition) in Bank bjb Syariah Rancaekek in financing iB Maslahah homeownership.This type of research is descriptive qualitative. Data collection techniques through observation, interviews, literature study, and documentation study. Data analysis used Miles and Huberman interaction.The research results show that the iB Maslahah home ownership financing in Islamic bank bjb has implemented the 5C aspect. However, of the five aspects, the dominant one taken into consideration is the character aspect. Analysis of character aspects is carried out through curriculum vitae, customer reputation in the work environment, conducting bank to bank information, looking for customer information in the neighborhood where he lives, looking at customer responsibilities, family circumstances, customer hobbies. Capacity is a slip or a detailed list of the customer's salary, other business fields owned, savings and current accounts related to the business carried out by the customer. Capital through the ownership status of the house where the previous customer lived, the type of transportation or vehicle the current customer has savings or savings owned. Collateral through collateral in the form of a house to be purchased by a customer with a loan from a bank. Condition through conjunctive conditions, government regulations, world political and economic situations, and other conditions that affect the market.